Knowledge and Attitude to Sexual and Reproductive Health Rights among Reproductive-Age Women (RAW) in Malete, Kwara State (Global Journal of Management and Business Research, 2019)
Sexual and reproductive health rights are essential human rights which are indisputable globally and therefore should be well known and embraced by all individuals. This study was purposely carried out to assess the knowledge and attitude to sexual and reproductive health rights among reproductive-age women (RAW) in Malete, Kwara State. A descriptive cross-sectional study of survey type was employed for the study. The sample for the study was drawn from the 5467 RAW in the study area using a multi-stage sampling technique. Sample size of 360 was determined with the aid of the Research Advisor application. Researcher-developed structured questionnaire which was validated by experts in related fields and tested for reliability using split-half technique was adopted for data collection. Frequency counts and percentages were used to analyse the data collected. This study showed that the knowledge of RAW about sexual and reproductive health rights was very low (17%); knowledge of sexually transmitted infections among RAW was moderate (56%); and knowledge of RAW about the benefits of family planning was low (35%). It was also revealed that RAW in Malete showed negative attitude to sexual behaviours like socializing with opposite sex, premarital sex etc. Based on these findings, increasing the knowledge of RAW in Malete through intensive awareness and advocacy campaign on sexual and reproductive health rights was recommended.
Keywords: knowledge; attitude; sexual and reproductive health rights; reproductive-age women; malete